2021
DOI: 10.1016/j.ijpddr.2021.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing in vitro approaches for screening anti-parasitic drugs against the brain-eating amoeba Naegleria fowleri

Abstract: Naegleria fowleri is both a pathogenic and a free-living microbial eukaryote, responsible for the development of primary amoebic meningoencephalitis (PAM) in humans. PAM is a rapid, severe and fatal underestimated infectious disease, which has been reported in countries with warmer climates. The major drawbacks with PAM are the lack of effective therapies and delay in diagnosis. The current frontline treatment presents a low rate of recovery (5%) and severe adverse effects. For example, many drug ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Moreover, this compound was the only one in which the anticyst activity is lower than the antitrophozoite one. The biochemical mechanism of the amphotericin B in N. fowleri is based on the lysis of the cell membrane and pore formation by binding to ergosterol and, hence, altering the membrane permeability ( 19 , 20 ). In the cystSt of N. fowleri , the cytoplasm is protected by a cyst wall whose composition is not clear ( 21 ); however, Chávez-Munguía et al reported the presence of enolase in the cyst wall ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this compound was the only one in which the anticyst activity is lower than the antitrophozoite one. The biochemical mechanism of the amphotericin B in N. fowleri is based on the lysis of the cell membrane and pore formation by binding to ergosterol and, hence, altering the membrane permeability ( 19 , 20 ). In the cystSt of N. fowleri , the cytoplasm is protected by a cyst wall whose composition is not clear ( 21 ); however, Chávez-Munguía et al reported the presence of enolase in the cyst wall ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a widely used process called drug repositioning that involves re-screening compounds with known biological activity and toxicity profiles has been found to be an effective strategy to accelerate drug discovery ( Xue et al, 2018 ; Martín-Escolano et al, 2021 ). However, the lack of standardized screening methods has stymied drug-repositioning efforts, with numerous studies relying on either the microscopy method or metabolically activated dyes (the resazurin microtiter method, the MTT colorimetric method) ( Duarte et al, 2009a ; Pothineni et al, 2016 ; Youssefi et al, 2017 ; Bailén et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%